Komunikasi Data melalui Jaringan Komunikasi Bergerak dengan Menggunakan GPRS - Sulystioko, Kukuh (Jurnal Informatika dan Komputasi STMIK Indonesia Jakarta, 2010)
GPRS is mobile communication and multimedia in using paket swichting technology. And then GPRS is radio modulation and transmission packets base systems use tunneling principle,  the same as GSM standard. Keywords: GPRS, GSM